1990
DOI: 10.1507/endocrj1954.37.319
|View full text |Cite
|
Sign up to set email alerts
|

Acute Decrease in Vitellogenin Synthesis by deprivation of food and Water in Laying Hens.

Abstract: Vitellogenin synthesis during a decrease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…First, gonadotropin and sex steroid levels declined quickly with the cessation of laying as early as Day 1 of the deprivation treatment and remained low during the molting period. Early declines in hormone levels related to egg laying during induced molts of the hen are well documented [2,6], and our results are in line with these reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, gonadotropin and sex steroid levels declined quickly with the cessation of laying as early as Day 1 of the deprivation treatment and remained low during the molting period. Early declines in hormone levels related to egg laying during induced molts of the hen are well documented [2,6], and our results are in line with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…Due to biological interest as well as economic importance, many studies have been conducted to clarify the hormonal mechanism of induced molting (see [2] for review). Increases in plasma thyroxine (T 4 ) and triiodothyronine (T 3 ) levels during induced molting have been reported [2][3][4][5][6], although these reports differ in the exact time course of the changes. Elevations of T3 and T4 have also been reported in natural seasonal molts of the hen [7] and some wild avian species [8,9].…”
mentioning
confidence: 99%
“…Three subtypes of VTGs have been identified in the chicken, among which VTGII is the most abundant [ 4 ]. Sekimoto et al found a close relationship between decreased egg production and lower VTG concentration in laying hens subjected to food and water deprivation [ 5 ]. Liou et al reported a positive correlation between serum level of VTG and total egg production in Taiwan red feathered chickens [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…48 : 197-204, 2002) vian thyroid hormones have been reported to affect not only heat production, metabolism and growth as in mammals, but also gonadal development, molting and migration (see [1][2][3] for review). The involvement of thyroid hormones in induced molt of the hen, where hens are forced into molting to improve egg production and egg quality, in particular has attracted the attention of investigators due to its biological interest as well as economic importance to the poultry industry [4][5][6]. Whether the natural seasonal molt is brought about by increased thyroid activity seems less certain, but t h e r e h a v e b e e n r e p o r t s s u g g e s t i n g t h e involvement of the thyroid in wild avian species (see [7] for review).…”
mentioning
confidence: 99%